2005
DOI: 10.1080/13625180500279847
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in sexual health: Problems and dilemmas

Abstract: A B S T R A C TThe increase in migrant populations in western Europe has led to specific problems and dilemmas in the area of sexual and reproductive health and service provision. In general, these problems and dilemmas can be divided into four categories: (1) epidemiology of diseases and risk factors; (2) psychosocial and cultural aspects; (3) communication; and (4) moral and ethical dilemmas.Regarding epidemiology, there is an increased prevalence in migrant groups of unwanted pregnancy and abortion, HIV/STD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 2 publications
0
21
0
3
Order By: Relevance
“…Tangmunkongvorakul et al [2] found similar results. Rademakers et al [23] stated that intercourse among Muslim young people were not appreciated before marriage, but men were tolerated more than girls. In a study about health staff's views related to adolescences' sexuality and abortion by Klingberg-Allvin et al [24], it was found out that midwives suggested that sexuality before marriage should be forbidden, however; doctors said that sexuality was a part of normal development, but it should still be delayed.…”
Section: Discussionmentioning
confidence: 98%
“…Tangmunkongvorakul et al [2] found similar results. Rademakers et al [23] stated that intercourse among Muslim young people were not appreciated before marriage, but men were tolerated more than girls. In a study about health staff's views related to adolescences' sexuality and abortion by Klingberg-Allvin et al [24], it was found out that midwives suggested that sexuality before marriage should be forbidden, however; doctors said that sexuality was a part of normal development, but it should still be delayed.…”
Section: Discussionmentioning
confidence: 98%
“…In Turkey friends and written and visual materials are more common among the sources of information of university students on the matter of sexuality (2)(3)(4)(5)(6)(7)(8). Studies show that as socio-economic level increases, the preferred sources of information change and written and visual materials (newspaper, magazines, and internet) is used more (17).…”
Section: Discussionmentioning
confidence: 99%
“…According to Çok et al (6) in general, premarital sexual intercourse for men is tolerated in Turkey, whereas women are expected to have no sexual experience before marriage. Rademakers et al (7) stated that this dilemma about virginity caused young Muslim girls to have virginity certificates or even hymen reconstruction. Sexuality is still seen as a taboo in Turkey and that is why sexual education, services and research are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were geographical differences in the behavioural changes, with the northern part of the country showing a smaller degree of change than other regions (Agha et al, 2001). Among migrants with different cultural backgrounds, not only language but also communication styles represent barriers to the negotiation of safer sex practices (Rademakers et al, 2005). The value of understanding local context and considering geographical differences was suggested in the management of programmes for commercial sex workers (Tuan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%